Comparison of Side Effects of COVID-19 Vaccines: Sinopharm, AstraZeneca, Sputnik V, and Covaxin in Women in Terms of Menstruation Disturbances, Hirsutism, and Metrorrhagia: A Descriptive-Analytical Cross-Sectional Study - Amirsaleh Abdollahi; Iman Naseh; Fatemeh Kalroozi; Mohammad Hassan Kazemi-Galougahi; Maryam Nezamzadeh; Shayan Sabeti Billandi; Mojtaba Yousefi Zoshk (International Journal of Fertility and Sterility, 2022)
Background: Present study assessed whether Sinopharm, AstraZeneca, Sputnik V, and Covaxin’s vaccinated womenreveal a distinct incidence of menstruation disturbances, hirsutism, and metrorrhagia.Materials and Methods: Data collection was performed from June to August 2021, and 427 women working in sevenselected hospitals in Tehran were studied in this descriptive-analytical cross-sectional study. All of these women hadreceived one or both doses of the vaccines with one of the assessed vaccines. Required data was collected via questionnaireand imported to SPSS 16 for further assessment and analysis. Fisher’s Exact Test and Chi-Squared test weremain statistical tests used to understand whether any significant relation exists or not.Results: The participant’s mean age and body mass index (BMI) were 29.78 ± 10.55 and 23.27 ± 3.82, respectively.Three hundred ninety-five cases (92.4%) had received both doses of the vaccines. Also, 154 cases (36.1%) had a historyof COVID-19. A total of 38 cases (8.8%) of menstruation disturbances, 20 cases (4.6%) of metrorrhagia, and 7cases (1.6%) of hirsutism were reported after receiving the vaccines. There was a significant difference among thevaccinated groups with the vaccines as mentioned earlier in terms of menstruation disturbances (hypermenorrhea,dysmenorrhea, Amenorrhea) (P=0.01). The highest and the lowest incidence of menstruation disturbances were recordedin the group vaccinated with Covaxin (17.6%) and Sputnik V (5%), respectively. There was also no significantdifference amongst the vaccinated groups with the four vaccines regarding the incidence of metrorrhagia andhirsutism (P=0.10 and P=0.12, respectively). There was no significant relationship between all three complicationsincidence with the previous infection concerning all vaccines (coefficient=0.46, 1.27, -0.15 respectively for menstruationdisturbances, metrorrhagia, and, hirsutism).Conclusion: Seemingly, Covaxin revealed the most side effects in terms of menstruation disturbances. As a result, professionalsmust carry out several studies with reasonable samples to recommend the vaccine to those women confidently.